2021
DOI: 10.1021/acs.joc.1c00394
|View full text |Cite
|
Sign up to set email alerts
|

Visible-Light-Promoted Diboron-Mediated Transfer Hydrogenation of Azobenzenes to Hydrazobenzenes

Abstract: A visible-light-promoted transfer hydrogenation of azobenzenes has been developed. In the presence of B2pin2 and upon visible-light irradiation, the reactions proceeded smoothly in methanol at ambient temperature. The azobenzenes with diverse functional groups have been reduced to the corresponding hydrazobenzenes with a yield of up to 96%. Preliminary mechanistic studies indicated that the hydrogen atom comes from the solvent and the transformation is achieved through a radical pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 61 publications
(33 reference statements)
1
22
0
Order By: Relevance
“…It is worth mentioning that the reaction time of the ortho-substituted azobenzenes is greatly shortened compared with the previously reported photochemical reactions. 8 Next, the applicability of unsymmetrical azobenzenes was evaluated (Scheme 3). As expected, the unsymmetrical azobenzenes with diverse substituents such as alkyl, cyano, alkoxy, ester, keto, and halogen were well tolerated to provide the desired products 4a−l in good yields.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…It is worth mentioning that the reaction time of the ortho-substituted azobenzenes is greatly shortened compared with the previously reported photochemical reactions. 8 Next, the applicability of unsymmetrical azobenzenes was evaluated (Scheme 3). As expected, the unsymmetrical azobenzenes with diverse substituents such as alkyl, cyano, alkoxy, ester, keto, and halogen were well tolerated to provide the desired products 4a−l in good yields.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The reaction mixture obtained from 1-chloro-3-nitrobenzene ( 7i ) (0.039 g) was heated for 17 h. Workup allowed the recovery of 1,2-bis(3-chlorophenyl)hydrazine ( 11i ) (0.031 g, 98%). 32 …”
Section: Experimental Sectionmentioning
confidence: 99%
“…The reaction mixture obtained from 1-chloro-3-nitrobenzene (7i) (0.039 g) was heated for 17 h. Workup allowed the recovery of 1,2-bis(3chlorophenyl)hydrazine (11i) (0.031 g, 98%). 32 Reduction of 1-Chloro-4-nitrobenzene (7j). The treatment of reaction crude obtained from 1-chloro-4-nitrobenzene (7j) (0.039 g), after heating for 17 h, allowed the recovery of 1,2bis(4-chlorophenyl)hydrazine (11j) (0.029 g, 92%).…”
Section: ■ Conclusionmentioning
confidence: 99%
“…[13] In 2021, Wang et al reported the hydrogenation of azobenzenes to hydrazobenzenes under visible light irradiation (Scheme 1d). [14] Shiraishi et al, [15] Wu et al, [16] and Zhu et al [17] reported hydrogenation reactions of azobenzenes to hydrazoarenes promoted by visible light irradiation (Scheme 1e).…”
Section: Introductionmentioning
confidence: 99%
“…In 2021, Wang et al. reported the hydrogenation of azobenzenes to hydrazobenzenes under visible light irradiation (Scheme 1d) [14] . Shiraishi et al., [15] Wu et al., [16] and Zhu et al [17] .…”
Section: Introductionmentioning
confidence: 99%